Magnetic particle-protein fiber dressing as well as preparation method and application thereof

Through the use of magnetic particles-protein fiber assembly and dressing, the directional arrangement of coated magnetic nanoparticles and functional proteins with copper ions is solved, and the problem of scar formation in tissue repair is achieved, and rapid scar repair and skin function is achieved. recover.

CN119236146AActive Publication Date: 2025-01-03TONGJI UNIV

Patent Information

Application Number
CN202411375353.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing tissue repair materials are prone to scar formation in the process of promoting wound healing, resulting in weakening of skin function and making it difficult to achieve rapid scar-free repair.

Method used

Using magnetic particles-protein fiber assembly and dressing, the combination of magnetic nanoparticles coated with copper ions and functional proteins is arranged in a directional manner under the action of magnetic fields to form colloidal fibers, synergistically acting on different stages of wound healing to reduce scar formation and restore skin function.

Benefits of technology

It achieves rapid scar-free repair, improves wound healing quality, reduces scar formation, and restores the functional integrity and aesthetics of the skin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236146A_ABST
    Figure CN119236146A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of scar-free skin injury repair, and particularly relates to a magnetic particle-protein fiber dressing and a preparation method and application thereof. The preparation method comprises the following steps: coating magnetic nano-particles, mixing the obtained coated magnetic nano-particles with water-soluble copper salt and water to carry out copper ion loading, and mixing the obtained coated magnetic nano-particles loaded with copper ions with functional protein and a buffer solution to carry out incubation. And placing the obtained magnetic microsphere-protein compound solution in an external magnetic field for magnetic attraction, and then carrying out directional assembly in the external magnetic field to obtain the magnetic particle-protein fiber assembly. According to the magnetic particle-protein fiber assembly and the magnetic particle-protein fiber coating modified medical dressing provided by the invention, scar-free rapid repair of wounds can be realized, and the completeness of skin functions can be recovered; and the preparation method is simple and has important clinical application value and market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of scarless skin damage repair, and specifically relates to a magnetic particle-protein fiber dressing and a preparation method and application thereof. Background Art

[0002] As the largest and strongest organ of the human body, the skin is the first barrier of the human body and can resist external damage or invasion of pathogenic microorganisms. However, in the face of nature, the skin is relatively fragile because it is exposed to the air and can be damaged by factors such as high temperature, scratches, and biochemical substances. In particular, chronic trauma, burns, and skin wound infections require arduous long-term treatment, which has become an important cause of serious harm to people's physical and mental health and reduced their quality of life and survival.

[0003] From "under-healing" (i.e., chronic / non-healing wounds) to "over-healing" (i.e., scarring / fibrosis), clinical wound healing problems are widespread. Wound healing consists of three classic phases: inflammation, proliferation, and remodeling. New insights show that these three phases overlap or occur in parallel in time and space of the wound (Baron JM, Glatz M, Proksch E. Optimal Support of Wound Healing: New Insights [J]. Dermatology, 2020, 236 (6): 593-600.). Broadly speaking, any disorder or interruption in wound healing at any stage will lead to healing beyond the normal range. In a narrow sense, they represent the two ends of the wound healing time curve. On the one hand, wound healing is slow. In the case of pressure / tissue ischemia, bacterial inflammation, or immune dysfunction (usually caused by systemic causes such as diabetes or atherosclerosis), the wound may not heal at all. Chronic non-healing wounds always maintain an open environment and are prone to complications. Infections may develop from the skin to the underlying structures, requiring surgical intervention or even amputation. On the other hand, there are scars that form after excessive healing.

[0004] At present, implantable medical devices for tissue repair are developing rapidly, and a variety of biomaterials such as antibacterial gauze, cotton balls, hydrogel films, microspheres, nanofibers, etc. have been developed. Although the above-mentioned implantable biomaterials can usually promote wound healing, scar formation caused by implantable biomaterials and rapid injury repair is still a difficult problem that needs to be solved. Because implants can cause complex immune responses in the body, while promoting the proliferation of fibroblasts and the deposition of a large amount of collagen, thereby causing fibrosis, fibrotic skin has weaker tensile strength than normal skin, and loses the integrity of skin function.

[0005] In summary, current tissue repair materials are still unable to achieve rapid, scar-free repair of the skin. Summary of the invention

[0006] The purpose of the present invention is to provide a magnetic particle-protein fiber assembly and a preparation method and application thereof, a magnetic particle-protein fiber dressing and a preparation method and application thereof. The magnetic particle-protein fiber assembly and magnetic particle-protein fiber dressing provided by the present invention can achieve rapid repair of wounds without scars and restore the integrity of skin function; and the preparation method is simple, and has important clinical application value and market prospects.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a magnetic particle-protein fiber assembly, comprising the following steps:

[0009] Coating the magnetic nanoparticles to obtain coated magnetic nanoparticles, wherein the coating material of the coated magnetic nanoparticles is a negatively charged polymer;

[0010] The coated magnetic nanoparticles, a water-soluble copper salt and water are mixed to load copper ions, thereby obtaining coated magnetic nanoparticles loaded with copper ions;

[0011] The copper ion-loaded coated magnetic nanoparticles, functional proteins and a buffer solution are mixed and incubated to obtain a magnetic microsphere-protein complex solution;

[0012] placing the magnetic microsphere-protein complex solution in an external magnetic field for magnetic attraction to obtain a magnetic composite microsphere intermediate assembly;

[0013] The resuspended liquid of the magnetic composite microsphere intermediate assembly is subjected to directional assembly under the control of a constant external magnetic field to obtain the magnetic particle-protein fiber assembly.

[0014] Preferably, the magnetic nanoparticles include one or more of Fe3O4 nanoparticles, γ-Fe2O3 nanoparticles, CoFe2O4 nanoparticles and Prussian blue nanoparticles;

[0015] The particle size of the magnetic nanoparticles is 1 to 300 nm.

[0016] Preferably, the negatively charged polymer comprises one or more of polydopamine, chitosan and hydroxymethyl cellulose;

[0017] The coating temperature is room temperature and the coating time is ≥ 8h;

[0018] The copper ion loading time is ≥12h;

[0019] The functional protein includes one or more of fibrinogen, albumin, collagen, fibronectin, laminin and cytokines;

[0020] The incubation time is 10 to 20 minutes;

[0021] The external magnetic field used in the magnetic attraction is provided by a magnetic frame, and the time of the magnetic attraction is 2 to 5 minutes.

[0022] Preferably, the magnetic field strength of the constant external magnetic field used in the directional assembly is 0.5 to 1 mT, and the time for the directional assembly is 10 to 30 minutes.

[0023] The present invention provides a magnetic particle-protein fiber assembly prepared by the preparation method described in the above technical scheme, comprising oriented colloidal fibers, wherein the colloidal fibers include a skeleton and functional proteins covering the surface of the skeleton, and the skeleton is formed by coated magnetic nanoparticles loaded with copper ions.

[0024] The present invention provides the use of the magnetic particle-protein fiber assembly described in the above technical solution in the preparation of scar-free wound healing materials.

[0025] The present invention provides a method for preparing a magnetic particle-protein fiber dressing, comprising the following steps:

[0026] Obtain a magnetic composite microsphere intermediate assembly according to the preparation method described in the above technical scheme;

[0027] The resuspension of the magnetic composite microsphere intermediate assembly is transferred to the surface of the substrate, and then oriented assembly is performed under the control of a constant external magnetic field to obtain the magnetic particle-protein fiber dressing.

[0028] Preferably, the substrate comprises one or more of methacrylated gelatin hydrogel, methacrylated hyaluronic acid hydrogel, sodium alginate hydrogel and PEG hydrogel;

[0029] The magnetic field strength of the constant external magnetic field used in the directional assembly is 0.5-1 mT, and the time of the directional assembly is 10-30 minutes.

[0030] The present invention provides a magnetic particle-protein fiber dressing prepared by the preparation method described in the above technical solution, comprising a substrate and a magnetic particle-protein fiber assembly arranged on the surface of the substrate;

[0031] The magnetic particle-protein fiber assembly comprises colloidal fibers arranged in a directional manner. The colloidal fibers comprise a skeleton and functional proteins covering the surface of the skeleton. The skeleton is formed by coated magnetic nanoparticles loaded with copper ions.

[0032] The present invention provides the use of the magnetic particle-protein fiber dressing described in the above technical solution in the preparation of a medical device for scar-free wound healing

[0033] The invention provides a preparation method of a magnetic particle-protein fiber assembly, comprising the following steps: coating magnetic nanoparticles to obtain coated magnetic nanoparticles, wherein the coating material of the coated magnetic nanoparticles is a negatively charged polymer; mixing the coated magnetic nanoparticles, a water-soluble copper salt and water to load copper ions to obtain coated magnetic nanoparticles loaded with copper ions; mixing the coated magnetic nanoparticles loaded with copper ions, a functional protein and a buffer solution to incubate to obtain a magnetic microsphere-protein complex solution; placing the magnetic microsphere-protein complex solution in an external magnetic field to perform magnetic attraction to obtain a magnetic composite microsphere intermediate assembly; and directional assembling the resuspended liquid of the magnetic composite microsphere intermediate assembly under the control of a constant external magnetic field to obtain a magnetic particle-protein fiber assembly. The present invention first uses a negatively charged polymer as a coating material to coat magnetic nanoparticles, obtains a negatively charged polymer coating material layer, and forms coated magnetic nanoparticles with a core-shell structure; then copper ions are loaded on the surface of the negatively charged polymer coating layer through electrostatic adsorption with the negatively charged polymer, and the coated magnetic nanoparticles loaded with copper ions are obtained. The magnetic microsphere-protein complex formed by incubating the coated magnetic nanoparticles loaded with copper ions and functional proteins forms a magnetic composite microsphere intermediate assembly under the action of an external magnetic field, and the magnetic composite microsphere intermediate assembly is in the shape of a colloidal fiber (including fibers with shorter lengths), and the magnetic composite microsphere intermediate assembly in the shape of a colloidal fiber is a skeleton surface composed of functional proteins uniformly covered on the coated magnetic nanoparticles loaded with copper ions. Finally, the present invention is regulated by a constant external magnetic field, and the colloidal fibers can be oriented and grown along the direction of the magnetic field lines to obtain a magnetic particle-protein fiber assembly. The preparation method provided by the present invention can conveniently realize the directional arrangement of colloidal fibers by controlling the magnetic field. At the same time, the skeleton structure of the coated magnetic nanoparticles of the functional protein and the copper ion loaded in the obtained colloidal fibers is highly stable, which simplifies the operation process and improves the therapeutic efficiency of the obtained magnetic particle-protein fiber assembly.

[0034] The present invention provides a magnetic particle-protein fiber assembly prepared by the preparation method described in the above technical solution, including colloidal fibers arranged in an orientation, wherein the colloidal fibers include a skeleton and functional proteins covering the surface of the skeleton, and the skeleton is formed by coated magnetic nanoparticles loaded with copper ions. In view of the three key stages of skin damage repair, namely bacterial infection, proliferation and remodeling, the present invention provides a magnetic particle-protein fiber assembly that can achieve three-stage full coverage and scar-free rapid repair. The basic skeleton and assembly unit of the magnetic particle-protein fiber assembly provided by the present invention adopt negatively charged polymer-functionalized magnetic nanoparticles with copper ion affinity (specifically Fe3O4@PDA-Cu magnetic nanoparticles in the embodiment of the present invention), which are combined with functional proteins to form colloidal fibers that can be arranged in an orientation under the induction of a magnetic field, and then constructed into a magnetic particle-protein fiber assembly. First, in the first stage (bacterial infection stage), the skeleton formed by the coated magnetic nanoparticles loaded with copper ions has good photothermal conversion performance and copper ion release ability, can reduce bacterial inflammation through the synergistic effect of photothermal and copper ions, can effectively remove bacteria, help reduce the risk of wound infection, and accelerate the wound healing process; at the same time, the coated magnetic nanoparticles loaded with copper ions have good biocompatibility, can reduce the stimulation and damage of the assembled materials to the tissue, and improve the safety and effectiveness of treatment. Secondly, in the second stage (proliferation stage) and the third stage (remodeling stage), the directional arrangement of the magnetic particle-protein fiber assembly provided by the present invention provides an orderly growth environment for cells and tissues, can accurately regulate cell migration, proliferation and remodeling processes, effectively avoid abnormal behavior of fibroblasts in the repair process, thereby reducing the formation of scars while ensuring rapid wound healing. At the same time, the copper ions in the skeleton formed by the coated magnetic nanoparticles loaded with copper ions can be continuously released within 28 days, and catalyze endogenous nitrosothiol (RSNO) to generate nitric oxide (NO), further promoting scar-free skin repair and restoring the integrity of skin function.

[0035] In summary, the magnetic particle-protein fiber assembly provided by the present invention has good biocompatibility and stability, and can play a synergistic role in different stages of tissue repair. At the same time, the multifunctional gas molecule NO is used to inhibit fibroblast differentiation, which can significantly improve the quality of wound healing, reduce scar formation, and restore the aesthetics and functionality of the skin.

[0036] The present invention provides a magnetic particle-protein fiber dressing prepared by the preparation method described in the above technical solution, comprising a substrate and a magnetic particle-protein fiber assembly arranged on the surface of the substrate; the magnetic particle-protein fiber assembly comprises oriented colloidal fibers, the colloidal fibers comprise a skeleton and functional proteins covering the surface of the skeleton, and the skeleton is formed by coated magnetic nanoparticles loaded with copper ions. The magnetic particle-protein fiber dressing provided by the present invention is used as a wound healing medical device and can be directly applied to wound healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A typical transmission electron microscopy image of Fe3O4@PDA-Cu;

[0038] Figure 2 This is the X-ray photoelectron spectroscopy technology diagram of Fe3O4@PDA-Cu;

[0039] Figure 3 Infrared thermal images of Fe3O4@PDA-Cu with different concentrations under near-infrared laser irradiation;

[0040] Figure 4 It is the TGA thermal analysis diagram of the assembly of Fe3O4@PDA-Cu and fibrinogen;

[0041] Figure 5 A typical transmission electron micrograph of the intermediate product of the assembly;

[0042] Figure 6 A typical scanning electron microscope photo of multifunctional magnetic particle-protein fiber;

[0043] Figure 7 Cumulative / non-cumulative release of copper ions from multifunctional magnetic particles-protein fibers within 28 days;

[0044] Figure 8 is the NO production of multifunctional magnetic particle-protein fiber within 14 days;

[0045] Fig. 9 It is a multifunctional magnetic particle-protein fiber dressing;

[0046] Fig.10 The therapeutic effect of multifunctional magnetic particle-protein fiber dressing on infected wounds in mice;

[0047] Fig.11 Staining of mouse healing skin tissue sections on day 14. DETAILED DESCRIPTION

[0048] The present invention provides a method for preparing a magnetic particle-protein fiber assembly, comprising the following steps:

[0049] Coating the magnetic nanoparticles to obtain coated magnetic nanoparticles, wherein the coating material of the coated magnetic nanoparticles is a negatively charged polymer;

[0050] The coated magnetic nanoparticles, a water-soluble copper salt and water are mixed to load copper ions, thereby obtaining coated magnetic nanoparticles loaded with copper ions;

[0051] The copper ion-loaded coated magnetic nanoparticles, functional proteins and a buffer solution are mixed and incubated to obtain a magnetic microsphere-protein complex solution;

[0052] placing the magnetic microsphere-protein complex solution in an external magnetic field for magnetic attraction to obtain a magnetic composite microsphere intermediate assembly;

[0053] The resuspended liquid of the magnetic composite microsphere intermediate assembly is subjected to directional assembly under the control of a constant external magnetic field to obtain the magnetic particle-protein fiber assembly.

[0054] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0055] The present invention coats magnetic nanoparticles to obtain coated magnetic nanoparticles, wherein the coating material of the coated magnetic nanoparticles is a negatively charged polymer. In the present invention, the coated magnetic nanoparticles include magnetic nanoparticles and a coating material coated on the surface of the magnetic nanoparticles. The magnetic nanoparticles preferably include one or more of Fe3O4 nanoparticles, γ-Fe2O3 nanoparticles, CoFe2O4 nanoparticles and Prussian blue nanoparticles. In a specific embodiment of the present invention, the magnetic nanoparticles are Fe3O4 nanoparticles. The particle size of the magnetic nanoparticles is preferably 1 to 300 nm.

[0056] In a specific embodiment of the present invention, when the magnetic nanoparticles are specifically selected as Fe3O4 nanoparticles, the preparation method of the Fe3O4 nanoparticles preferably includes the following steps: mixing an inorganic water-soluble iron salt, polyacrylic acid, urea and an alcohol solvent for a solvothermal reaction to obtain Fe3O4 nanoparticles. The inorganic water-soluble iron salt is preferably one or more of ferric chloride, ferric nitrate and ferric sulfate. The alcohol solvent is preferably ethylene glycol. The mass ratio of the inorganic water-soluble iron salt, polyacrylic acid and urea is preferably (0.8-0.85): (0.25-0.3): (1.5-2), and can be specifically selected as 0.81: 0.29: 1.8. The present invention has no special requirements for the amount of the alcohol solvent. The mixing of the inorganic water-soluble iron salt, polyacrylic acid, urea and the alcohol solvent is preferably carried out under ultrasonic conditions, and the solvothermal reaction is preferably carried out in a stainless steel reactor with a polytetrafluoroethylene liner. The temperature of the solvothermal reaction is preferably 200-300°C. The time of the solvothermal reaction is preferably ≥ 12h. The solid product obtained by the hydrothermal reaction is preferably washed with ethanol and then with water in sequence to obtain Fe3O4 nanoparticles. The ethanol washing is preferably carried out under ultrasonic conditions. The water washing is preferably ultrapure water washing or deionized water washing, and the water washing is preferably carried out under ultrasonic conditions. The number of water washings is preferably 3 to 5 times. The time for ethanol washing is preferably 5 to 10 minutes, and the time for each water washing is preferably 5 to 10 minutes. In the present invention, the obtained Fe3O4 nanoparticles are dispersed in deionized water and stored at 4°C.

[0057] In the present invention, the coating material is a loaded polymer. In the present invention, the negatively charged polymer includes one or more of polydopamine, chitosan and hydroxymethyl cellulose. In a specific embodiment of the present invention, the negatively charged polymer is specifically polydopamine.

[0058] In the present invention, when the negatively charged polymer is specifically chitosan and / or hydroxymethyl cellulose, the present invention preferably uses chitosan and / or hydroxymethyl cellulose to directly coat the magnetic nanoparticles in a solution environment. The present invention has no special requirements for the specific implementation process of the chitosan and / or hydroxymethyl cellulose coating.

[0059] In the present invention, when the negatively charged polymer is specifically polydopamine, the coating process preferably comprises the following steps:

[0060] Magnetic nanoparticles, dopamine and buffer are mixed, and polymerization coating is performed under alkaline conditions to obtain coated magnetic nanoparticles, wherein the coating material of the coated magnetic nanoparticles is polydopamine. In the present invention, the mass ratio of the Fe3O4 nanoparticles and the dopamine is preferably 3:(1-3). The buffer is preferably Tris-HCl, the pH value of the Tris-HCl is preferably 8.5, and the molar concentration of Tris-HCl is preferably 10mM. The mixing of the magnetic nanoparticles, the polymerization monomer and the buffer is preferably performed under ultrasonic conditions. The temperature of the polymerization coating is preferably room temperature, and the time of the polymerization coating is preferably ≥8h.

[0061] In a specific embodiment of the present invention, when the polymerization monomer is dopamine (DA), the present invention obtains a polydopamine (PDA) coating layer by oxidative polymerization of dopamine on the carboxyl surface of Fe3O4 under alkaline conditions to form a Fe3O4@PDA coating material with a core-shell structure.

[0062] In the present invention, the solid product obtained by the polymerization coating is preferably washed with ethanol and washed with water in sequence to obtain coated magnetic nanoparticles. The ethanol washing is preferably carried out under ultrasonic conditions. The water washing is preferably ultrapure water washing or deionized water washing, and the water washing is preferably carried out under ultrasonic conditions. The number of water washings is preferably 3 to 5 times. The time for the ethanol washing is preferably 5 to 10 minutes, and the time for each water washing is preferably 5 to 10 minutes.

[0063] After obtaining the coated magnetic nanoparticles, the present invention mixes the coated magnetic nanoparticles, water-soluble copper salt and water for copper ion loading to obtain coated magnetic nanoparticles loaded with copper ions. In the present invention, the water-soluble copper salt is preferably one or more of copper chloride, copper nitrate and copper sulfate. The water is preferably deionized water. In a specific embodiment of the present invention, the water-soluble copper salt is specifically preferably CuCl2·2H2O. The mixing of the coated magnetic nanoparticles, the water-soluble copper salt and water preferably includes: dissolving the water-soluble copper salt in water to obtain a copper salt solution; dispersing the coated magnetic nanoparticles in the copper salt solution. The molar concentration of the copper salt solution is preferably 1mM. The dispersion is preferably carried out under ultrasonic conditions. The temperature of the copper ion loading is preferably room temperature, and the time of the copper ion loading is preferably ≥12h. The copper ion loading is preferably carried out under stirring conditions.

[0064] In a specific embodiment of the present invention, dopamine is first oxidized and polymerized on the carboxyl surface of Fe3O4 under alkaline conditions to obtain a polydopamine (PDA) coating layer to form a Fe3O4@PDA coating material with a core-shell structure; then copper ions are complexed with the catecholamine groups of PDA to form Fe3O4@PDA-Cu magnetic nanoparticles through non-covalent interactions.

[0065] In the present invention, the solid product obtained by the copper ion loading is preferably washed with water to obtain the coated magnetic nanoparticles loaded with copper ions. The water washing is preferably ultrapure water washing or deionized water washing, the water washing is preferably carried out under ultrasonic conditions, and the number of times of the water washing is preferably 3 to 5 times. The time of each water washing is preferably 5 to 10 minutes.

[0066] After obtaining the coated magnetic nanoparticles loaded with copper ions, the present invention mixes the coated magnetic nanoparticles loaded with copper ions, functional proteins and buffer solution for incubation to obtain a magnetic microsphere-protein complex solution. In the present invention, the functional protein preferably includes one or more of fibrinogen, albumin, collagen, fibronectin, laminin and cytokines. In the present invention, the cytokine is a protein mixture secreted by cells, and the general method for obtaining cytokines is: culture the cells for a certain period of time, and take the supernatant and mix it with magnetic beads. In a specific embodiment of the present invention, the functional protein is specifically fibrinogen. The buffer solution is preferably PBS. The mixing of the coated magnetic nanoparticles loaded with copper ions, functional proteins and buffer solution preferably includes: dissolving the functional protein in a buffer solution to obtain a protein solution; mixing the protein solution with the coated magnetic nanoparticles loaded with copper ions. The mass concentration of the protein solution is preferably 0.1 mg / mL. The incubation is preferably carried out under slow shaking conditions, the incubation temperature is preferably 1 to 4°C, and the incubation time is preferably 10 to 20 minutes.

[0067] After obtaining the magnetic microsphere-protein complex solution, the present invention places the magnetic microsphere-protein complex solution in an external magnetic field for magnetic attraction to obtain a magnetic composite microsphere intermediate assembly. In the present invention, the external magnetic field used for the magnetic attraction is preferably provided by a magnetic frame. In a specific embodiment of the present invention, the present invention preferably places the magnetic microsphere-protein complex solution on the magnetic frame for standing. The time of the magnetic attraction is preferably 2 to 5 minutes. The magnetic attraction is preferably carried out under static conditions. After the magnetic attraction is completed, black agglomerates are formed on the wall of the vessel, and the external magnetic field is removed.

[0068] The present invention preferably resuspends the magnetic composite microsphere intermediate assembly obtained by magnetic absorption on the vessel wall to obtain a resuspension of the magnetic composite microsphere intermediate assembly, and performs subsequent directional assembly on the resuspension of the magnetic composite microsphere intermediate assembly.

[0069] After obtaining the intermediate assembly of magnetic composite microspheres, the resuspension of the intermediate assembly of magnetic composite microspheres is directed and assembled under the control of a constant external magnetic field to obtain a magnetic particle-protein fiber assembly. In the present invention, the specific setting method of the constant external magnetic field is preferably: magnets are placed on both sides or one side of the container containing the resuspension of the intermediate assembly of magnetic composite microspheres. Specifically, the specific setting method of the constant external magnetic field is preferably the first case and the second case. The first case: On both sides of any direction of the container containing the resuspension of the intermediate assembly of magnetic composite microspheres, a permanent magnet with the same magnetic flux is placed in parallel to keep the intermediate assembly material of magnetic composite microspheres in the resuspension from having a magnetic surge phenomenon. The second case: A magnet is placed in any direction of the container containing the resuspension of the intermediate assembly of magnetic composite microspheres, and the distance between the magnet and the container containing the resuspension of the intermediate assembly of magnetic composite microspheres is set, as long as the intermediate assembly material of magnetic composite microspheres in the resuspension does not have a strong magnetic surge phenomenon. In the present invention, in the second case, the magnet is preferably an 80mT magnet, and the distance between the magnet and the container containing the heavy suspension of the magnetic composite microsphere intermediate assembly is 2.5cm. In the above two configurations of the constant external magnetic field, the present invention can form a directional assembly, and the orientation direction is parallel to the magnetic field direction. In the present invention, the magnetic field strength of the constant external magnetic field used for the directional assembly is 0.5-1mT, and the time of the directional assembly is 10-30min. The directional assembly is preferably carried out under static conditions. The present invention preferably can effectively achieve the binding stability between the functional protein in the colloidal fiber and the skeleton formed by the coated magnetic nanoparticles loaded with copper ions through the directional assembly, and is conducive to the growth and directional assembly of the colloidal fiber.

[0070] The present invention provides a magnetic particle-protein fiber assembly prepared by the preparation method described in the above technical scheme, comprising oriented colloidal fibers, wherein the colloidal fibers include a skeleton and functional proteins covering the surface of the skeleton, and the skeleton is formed by coated magnetic nanoparticles loaded with copper ions.

[0071] The present invention provides the use of the magnetic particle-protein fiber assembly described in the above technical solution in the preparation of scar-free wound healing materials.

[0072] The present invention provides a method for preparing a magnetic particle-protein fiber dressing, comprising the following steps:

[0073] Obtain a magnetic composite microsphere intermediate assembly according to the preparation method described in the above technical scheme;

[0074] The resuspension of the magnetic composite microsphere intermediate assembly is transferred to the surface of the substrate, and then oriented assembly is performed under the control of a constant external magnetic field to obtain the magnetic particle-protein fiber dressing.

[0075] The present invention obtains a magnetic composite microsphere intermediate assembly according to the preparation method described in the above technical solution. The preparation process of the magnetic composite microsphere intermediate assembly will not be described in detail here.

[0076] After obtaining the intermediate assembly of magnetic composite microspheres, the present invention transfers the resuspension of the intermediate assembly of magnetic composite microspheres to the surface of the substrate, and performs directional assembly under the control of a constant external magnetic field to obtain the magnetic particle-protein fiber dressing. In the present invention, the substrate preferably includes one or more of methacryloyl gelatin hydrogel, methacryloyl hyaluronic acid hydrogel, sodium alginate hydrogel and PEG hydrogel. In the present invention, the PEG hydrogel is specifically poly (ethylene glycol) diacrylate.

[0077] The magnetic field strength of the constant external magnetic field used in the directional assembly is preferably 0.5 to 1 mT, and the time for the directional assembly is preferably 10 to 30 min.

[0078] In a specific embodiment of the present invention, the preparation method of the methacrylated gelatin hydrogel preferably includes the following steps: dissolving methacrylated gelatin (GelMA) powder in a photocrosslinker solution to obtain a hydrogel precursor solution; subjecting the hydrogel precursor solution to a crosslinking reaction under ultraviolet light to obtain a methacrylated gelatin hydrogel. The photocrosslinker solution includes a photocrosslinker and a PBS buffer, and the photocrosslinker is preferably lithium phenyl-2,4,6-trimethylbenzoylphosphinate. The mass ratio of the GelMA powder to the photocrosslinker is preferably 10:12.5. The wavelength of the ultraviolet light is preferably 405 nm. The time of the crosslinking reaction is preferably 1 min.

[0079] The present invention provides a magnetic particle-protein fiber dressing prepared by the preparation method described in the above technical solution, comprising a substrate and a magnetic particle-protein fiber assembly arranged on the surface of the substrate;

[0080] The magnetic particle-protein fiber assembly comprises colloidal fibers arranged in a directional manner. The colloidal fibers comprise a skeleton and functional proteins covering the surface of the skeleton. The skeleton is formed by coated magnetic nanoparticles loaded with copper ions.

[0081] The present invention provides the use of the magnetic particle-protein fiber dressing described in the above technical solution in the preparation of a medical device for scar-free wound healing.

[0082] The magnetic particle-protein fiber dressing provided by the present invention is aimed at the first stage of tissue repair, and the functionalized nanoparticles reduce bacterial inflammation through the synergistic effect of photothermal and copper ions. For the second and third stages, the oriented colloidal fibers can induce fibroblasts and collagen to be arranged in an orderly manner at the spatial level. On the other hand, within the time range, copper ions can be continuously released within 28 days and catalyze endogenous RSNO to generate NO, synergistically promoting scar-free skin repair and restoring the integrity of skin function.

[0083] In a specific embodiment of the present invention, the preparation method of the magnetic particle-protein fiber assembly provided by the present invention comprises the following steps: mixing Fe3O4 nanoparticles, dopamine and buffer solution, and performing polymerization coating under alkaline conditions to obtain Fe3O4@PDA coating material; mixing the Fe3O4@PDA coating material, water-soluble copper salt and water for copper ion loading to obtain Fe3O4@PDA-Cu magnetic nanoparticles; mixing the Fe3O4@PDA-Cu magnetic nanoparticles, fibrinogen, water and buffer solution for incubation to obtain a magnetic microsphere-protein complex solution; placing the magnetic microsphere-protein complex solution in an external magnetic field for magnetic attraction to obtain a magnetic composite microsphere intermediate assembly; and directional assembling the resuspension of the magnetic composite microsphere intermediate assembly under the control of a constant external magnetic field to obtain a magnetic particle-protein fiber assembly. The present invention firstly obtains a polydopamine (PDA) coating layer on the carboxyl surface of Fe3O4 by oxidative polymerization of dopamine under alkaline conditions, thereby forming a Fe3O4@PDA coating material with a core-shell structure; then copper ions are complexed with the catecholamine groups of PDA to form Fe3O4@PDA-Cu magnetic nanoparticles through non-covalent interactions. The magnetic microsphere-protein complex formed by incubating Fe3O4@PDA-Cu magnetic nanoparticles and fibrinogen forms a magnetic composite microsphere intermediate assembly under the action of an external magnetic field. The magnetic composite microsphere intermediate assembly is in the shape of colloidal fibers, and the colloidal fibers are the skeleton surface composed of fibrinogen uniformly covered on the Fe3O4@PDA-Cu magnetic nanoparticles; finally, the present invention regulates the static magnetic field, so that the colloidal fibers can be oriented along the direction of the magnetic field lines to obtain a magnetic particle-protein fiber assembly. The preparation method provided by the present invention can conveniently realize the oriented arrangement of the colloidal fibers through the control of the magnetic field, simplify the operation process, and improve the therapeutic efficiency of the obtained magnetic particle-protein fiber assembly.

[0084] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0085] Example 1

[0086] (1) Accurately weigh 0.81 g of ferric chloride, 0.29 g of polyacrylic acid, and 1.8 g of urea, disperse the above reagents in 30 mL of ethylene glycol, stir and dissolve them by ultrasonic stirring, transfer them to a reactor, heat them in a high-temperature oven at 200° C. for 12 h, and prepare the superparamagnetic Fe3O4 nanoparticle core by a hydrothermal synthesis one-pot method. After the reaction is completed, wait for the reactor to cool to room temperature, and ultrasonically disperse the obtained black precipitate in ethanol for 5 to 10 min. After magnetic separation, disperse the precipitate in deionized water again, ultrasonically separate for 5 to 10 min, and use an external magnetic field for magnetic separation. Repeatedly wash with deionized water for 3 to 5 times, and finally disperse it in deionized water to obtain a Fe3O4 superparamagnetic core with a particle size of 100 nm. The transmission electron microscopy image of the Fe3O4 superparamagnetic core prepared in this embodiment is shown in FIG. Figure 1 The X-ray photoelectron spectroscopy technology diagram of the Fe3O4 superparamagnetic core prepared in this embodiment is shown in FIG. Figure 2 shown.

[0087] (2) Take 30 mg of the product in step (1) and disperse it in 120 mL Tris-HCl (10 mM, pH = 8.5). After ultrasonic treatment for 30 min, add 30 mg DA and fully ultrasonically dissolve it. The mixture is continuously stirred at 200 rpm for 8 h at room temperature. After the reaction is completed, the obtained product is dispersed in ethanol and ultrasonically dispersed for 5 to 10 min. After magnetic separation, the precipitate is dispersed in deionized water again, ultrasonically dispersed for 5 to 10 min, magnetically separated by an external magnetic field, repeatedly washed with deionized water for 3 to 5 times, and finally dispersed in deionized water. Fe3O4@PDA with a hydraulic diameter of about 150 nm is obtained.

[0088] (3) Add 6.82 mg of CuCl2·2H2O to 40 mL of deionized water, ultrasonically disperse the product in step (2) in the CuCl2 solution, and stir at room temperature for 12 h. Separate the obtained product, collect it with a magnet, and wash it three times with ultrapure water to obtain Fe3O4@PDA-Cu. Figure 3 Infrared thermal images of Fe3O4@PDA-Cu with different concentrations prepared using PBS buffer under near-infrared laser irradiation.

[0089] (4) Accurately weigh 1 mg of fibrinogen and place it in a centrifuge tube, add 1 mL of PBS solution to prepare a protein solution (protein concentration 1 mg / mL), and dilute it to 0.1 mg / mL with PBS. Pipette the aqueous dispersion containing 100 μg of Fe3O4@PDA-Cu prepared in step (3), add it to the protein solution, gently flip the centrifuge tube, incubate at 4°C or room temperature for 10 minutes, and obtain a PBS liquid phase system of magnetic microsphere-protein complex. The product does not need to be washed and is set aside;

[0090] (5) Place the PBS liquid phase system of the magnetic microsphere-protein complex in step (4) on a magnetic stand and let it stand for 2 minutes. After black aggregates form on the wall of the vessel, remove the external magnetic field; gently blow with a pipette tip to resuspend and transfer to a well plate with a cover glass on the bottom (the cover glass is placed to facilitate the subsequent direct characterization of the assembly morphology). The transmission electron microscopy photograph of the intermediate assembly of the magnetic composite microspheres is shown in Figure 2. Figure 5 As shown. A constant external magnetic field of about 0.5 mT is applied on both sides of the well plate, and the reaction is allowed to stand for 10 minutes, and a magnetic particle-protein fiber assembly is obtained on the surface of the cover glass. The cover glass at the bottom is slowly removed with tweezers, and the morphology and size of the magnetic particle-protein fiber assembly can be directly observed under an optical microscope. Under typical conditions, the magnetic particle-protein fiber assembly presents a linear structure, such as Figure 6 As shown, the diameter of a single fiber is 2 μm and the diameter of the cross-linked fibers is 15 μm. Figure 4 This is the TGA thermal analysis diagram of the magnetic particle-protein fiber assembly prepared in this example. Figure 6 This is a scanning electron microscope photograph of the magnetic particle-protein fiber assembly prepared in this example.

[0091] Example 2

[0092] (1) Preparation of hydrogel dressing: Take 20 mL of PBS buffer and add 50 mg of lithium phenyl-2,4,6-trimethylbenzoylphosphinate. Heat the above solution at 50°C for 15 min and store at 4°C for later use. Weigh 10 mg of GelMA dry powder and dissolve it in 5 mL of lithium phenyl-2,4,6-trimethylbenzoylphosphinate solution prepared in advance, and heat at 60°C for 30 min to obtain a hydrogel precursor solution. Irradiate the hydrogel precursor solution with 405 nm ultraviolet light for 1 min to obtain a hydrogel dressing.

[0093] (2) Preparation of a directional multifunctional magnetic particle-protein fiber dressing: Place the hydrogel dressing obtained in step (1) at the bottom of a 24-well plate. Place the PBS liquid phase system of the magnetic microsphere-protein complex obtained in step (4) of Example 1 on a magnetic rack and let it stand for 2 minutes. After black agglomerates are formed on the wall of the vessel, remove the external magnetic field; gently blow with a pipette tip to resuspend and transfer to the well plate with a hydrogel dressing on the bottom (the hydrogel dressing is placed to facilitate subsequent in vivo application). Apply a constant external magnetic field of about 0.5 mT on both sides of the well plate, let it stand and react for 30 minutes, and obtain a magnetic particle-protein fiber assembly on the surface of the hydrogel to obtain a magnetic particle-protein fiber dressing. Use tweezers to slowly clamp out the magnetic particle-protein fiber dressing at the bottom. Fig. 9 This is a physical picture of the multifunctional magnetic particle-protein fiber dressing prepared in this example.

[0094] Comparative Example 1

[0095] Magnetic nanoparticle-protein self-assembly: Place the hydrogel dressing obtained in step (1) of Example 2 at the bottom of a 24-well plate. Place the PBS liquid phase system of the magnetic microsphere-protein complex obtained in step (4) of Example 1 on a magnetic stand and let it stand for 2 minutes. After black aggregates form on the wall of the vessel, remove the external magnetic field; gently blow with a pipette tip to resuspend and transfer to the well plate with the hydrogel dressing at the bottom. Let it stand for 30 minutes to form non-oriented magnetic particle-protein fibers on the surface of the hydrogel.

[0096] Comparative Example 1 shows that electrostatic self-assembly can also form fibers on the surface of the hydrogel, but the network is intricate and does not have a directional morphology, which does not conform to the growth habits of fibroblasts in skin repair. Although the product prepared in Comparative Example 1 can be found to have a certain fiber orientation from the morphology in the electron microscope photo, the fibers are not completely arranged in a straight line, and different columns are intersected to form a network structure. In Example 2 of the present invention, the present invention uses a magnetic field to intervene in the directional assembly process on the surface of the substrate material, and the obtained dressing product is a completely directional assembly fiber, almost completely parallel. This is because, in the absence of an external magnetic field (Comparative Example 1), the geomagnetic field interferes with the self-assembly, but because the magnetic field is relatively weak, the obtained fibers have a certain degree of arrangement. When the magnetic field is increased to the range described in Example 2, the magnetic field can guide the assembly materials to be arranged along the direction of the magnetic field, with a higher degree of arrangement. In summary, compared with Comparative Example 1, the magnetic protein fibers prepared in the embodiment of the present invention have a higher degree of arrangement.

[0097] Example 3

[0098] (1) In the in vitro experiment, in order to monitor the copper ion release ability of the multifunctional magnetic particle-protein fiber dressing prepared in Example 2, the multifunctional magnetic particle-protein fiber dressing was soaked in 1 mL of PBS, and the PBS solution was collected on the 1st day, 3rd day, 6th day, 9th day, 14th day, 21st day, and 28th day for inductively coupled plasma mass spectrometry testing, and fresh PBS was added immediately after each collection. Figure 7 Cumulative / non-cumulative release of copper ions within 28 days of the multifunctional magnetic particle-protein fiber dressing prepared in Example 2. Figure 7 It can be seen that the multifunctional magnetic particle-protein fiber dressing prepared in Example 2 can achieve continuous release of copper ions for 28 days.

[0099] (2) Monitoring of NO catalytic production ability: The multifunctional magnetic particle-protein fiber dressing was immersed in 1 mL of PBS using a procedure similar to step (1). NO donors (10 μM S-nitroso-N-acetylpenicillamine and 10 μM reduced glutathione) were added every 6 h, and the NO production was detected by the classic Griess Reagent method for 14 consecutive days. Figure 8 This is the NO generation within 14 days of the multifunctional magnetic particle-protein fiber dressing prepared in Example 2.

[0100] Example 4

[0101] (1) For in vivo experiments, 10 BALB / C mice (five per group) were purchased from Jiangsu Jicui Yaokang Biotechnology Co., Ltd. to verify the therapeutic effect of skin wounds. The mice were housed in an SPF-grade environment in the experimental animal center. BALB / C male mice (6-8 weeks old) were individually caged for 1 week with free access to food and water. The mice were given general anesthesia with 3% isoflurane using a small animal anesthesia system for at least 5 minutes, and the hair was removed from the dorsal side of the mice with electric clippers and depilatory (hair removal) cream was applied with a cotton swab. General anesthesia was continued as described above to ensure that the mice would not wake up during the subsequent surgical procedure, and the skin was wiped with 70% ethanol. After drying, the skin was rinsed with PBS. Two full-thickness wounds were extended through the fascia membrane on the dorsal side of the midline on both sides using an 8-mm biopsy punch. 100 μL of a mixed suspension of Staphylococcus aureus and Escherichia coli (1×10 8 CFU / mL).

[0102] (2) Wound healing analysis: The skin repair material was placed on the back wound of the mouse (the control group and the magnetic particle-protein fiber dressing group prepared in Example 2, respectively). A circular reference was prepared and placed next to the wound. Wound photos were taken with a digital camera on the 0th, 3rd, 7th, and 14th days of the experiment until the wound was completely closed. After the experiment, the mice were anesthetized with 3% isoflurane for at least 5 minutes and euthanized by cervical dislocation. Paraffin sections and HE staining were performed on the wound healing sites of the mouse skin. Fig.10 The therapeutic effect of multifunctional magnetic particle-protein fiber dressing on infected wounds in mice; Fig.11 Staining of mouse healing skin tissue sections on day 14. Fig.10 and Fig.11 It can be seen that compared with the control group, the multifunctional magnetic particle-protein fiber dressing prepared in Example 2 of the present invention can achieve rapid repair of skin injuries without scars.

[0103] From the above examples, it can be seen that the present invention can conveniently realize the directional arrangement of colloidal fibers through the control of magnetic field, simplify the operation process, and improve the treatment efficiency. The method provides a new perspective and method for scarless healing research by integrating directional morphology and biological clues. By precisely controlling the morphology and biological activity of the material, more precise regulation is achieved in the wound healing process. The present invention designs polydopamine-functionalized magnetic nanoparticles with copper ion affinity. This design not only gives the nanoparticles excellent biocompatibility and stability, but also gives them unique magnetic responsiveness and copper ion binding ability. It can reduce bacterial inflammation through the synergistic effect of photothermal and metal ions, help reduce the risk of wound infection, and accelerate the wound healing process. Polydopamine-functionalized magnetic nanoparticles have good biocompatibility, can reduce the stimulation and damage of materials to tissues, and improve the safety and effectiveness of treatment. Under the induction of the magnetic field, the colloidal fibers formed by the combination of polydopamine-functionalized magnetic nanoparticles and fibrinogen can be oriented along the direction of the magnetic field lines to form a micron-sized fibrinogen scaffold. This directional arrangement provides an orderly growth environment for cells and tissues. The system designed by the present invention can play a synergistic role in different stages of tissue repair. The multifunctional gas molecule NO is used to inhibit fibroblast differentiation, providing new ideas and insights for scarless skin repair. It can significantly improve the quality of wound healing, reduce scar formation, and restore the beauty and functionality of the skin.

[0104] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a magnetic particle-protein fiber assembly, characterized in that: The following steps are involved: Coating the magnetic nanoparticles to obtain coated magnetic nanoparticles, wherein the coating material of the coated magnetic nanoparticles is a negatively charged polymer; The coated magnetic nanoparticles, a water-soluble copper salt and water are mixed to load copper ions, thereby obtaining coated magnetic nanoparticles loaded with copper ions; The copper ion-loaded coated magnetic nanoparticles, functional proteins and a buffer solution are mixed and incubated to obtain a magnetic microsphere-protein complex solution; placing the magnetic microsphere-protein complex solution in an external magnetic field for magnetic attraction to obtain a magnetic composite microsphere intermediate assembly; The resuspended liquid of the magnetic composite microsphere intermediate assembly is subjected to directional assembly under the control of a constant external magnetic field to obtain the magnetic particle-protein fiber assembly.

2. The preparation method according to claim 1, characterized in that: The magnetic nanoparticles include one or more of Fe3O4 nanoparticles, γ-Fe2O3 nanoparticles, CoFe2O4 nanoparticles and Prussian blue nanoparticles; The particle size of the magnetic nanoparticles is 1 to 300 nm.

3. The preparation method according to claim 1, characterized in that: The negatively charged polymer includes one or more of polydopamine, chitosan and hydroxymethyl cellulose; The coating temperature is room temperature and the coating time is ≥ 8h; The copper ion loading time is ≥12h; The functional protein includes one or more of fibrinogen, albumin, collagen, fibronectin, laminin and cytokines; The incubation time is 10 to 20 minutes; The external magnetic field used in the magnetic attraction is provided by a magnetic frame, and the time of the magnetic attraction is 2 to 5 minutes.

4. The preparation method according to claim 1 or 3, characterized in that: The magnetic field strength of the constant external magnetic field used in the directional assembly is 0.5-1 mT, and the time of the directional assembly is 10-30 minutes.

5. The magnetic particle-protein fiber assembly prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The invention comprises directional colloidal fibers, wherein the colloidal fibers comprise a skeleton and functional proteins covering the surface of the skeleton, and the skeleton is formed by coated magnetic nanoparticles loaded with copper ions.

6. Use of the magnetic particle-protein fiber assembly according to claim 5 in the preparation of scarless wound healing materials.

7. A method for preparing a magnetic particle-protein fiber dressing, characterized in that: The following steps are involved: Obtaining a magnetic composite microsphere intermediate assembly according to the preparation method of any one of claims 1 to 4; The resuspension of the magnetic composite microsphere intermediate assembly is transferred to the surface of the substrate, and then oriented assembly is performed under the control of a constant external magnetic field to obtain the magnetic particle-protein fiber dressing.

8. The preparation method according to claim 7, characterized in that: The substrate comprises one or more of methacryloyl gelatin hydrogel, methacryloyl hyaluronic acid hydrogel, sodium alginate hydrogel and PEG hydrogel; The magnetic field strength of the constant external magnetic field used in the directional assembly is 0.5-1 mT, and the time of the directional assembly is 10-30 minutes.

9. The magnetic particle-protein fiber dressing prepared by the preparation method according to claim 7 or 8, characterized in that: It comprises a substrate and a magnetic particle-protein fiber assembly arranged on the surface of the substrate; The magnetic particle-protein fiber assembly comprises colloidal fibers arranged in a directional manner. The colloidal fibers comprise a skeleton and functional proteins covering the surface of the skeleton. The skeleton is formed by coated magnetic nanoparticles loaded with copper ions.

10. Use of the magnetic particle-protein fiber dressing according to claim 9 in the preparation of a medical device for scar-free wound healing.

Citation Information

Patent Citations

  • Magnetically therapeutic antibacterial haemostatic wound dressing and preparation method thereof

    CN105169460A

  • Magnetic flexible carrier Fe3O4-PDA-DAS preparation method and application thereof

    CN107988198A

  • Article and dressing for improved healing and methods of use

    US20220339459A1

Cited By

  • Anti-infection scar-free healing promoting tissue repair material as well as preparation method and application thereof

    CN121754735A